MEMPERBAIKI PEREKONOMIAN DENGAN UPAYA MEMBANGUN SISTEM - Sukarno, Bedjo (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2006)
ABSTRACT People’s anguish and concern towards the bad circumstance in Indonesia should be one of significant aspect to redevelop the economy. Furthermore, investment atmosphere is urgently improved in this circumstance. Political stability will give a great contribution towards economical stability, and in reverse, economical stability is on a must to create a political stability. Investment atmosphere in Indonesia’s bad circumstance should be improved by a collective awareness and real movements from government and civil society. That is related to the weakness of law enforcement, political-social stability and civil security in Indonesia. The crisis in real sector that is showed by the high unemployment and poverty rates is caused by the instability in investment, both domestic and foreign investments. Keywords: building a system, economic growth, investment